Influence of sire on quality of beef - Mackintosh, D.L.; Kropf, Donald H.; Good, D.L.; Wheat, J.D.; Teagarden, J.; Harrison, D.L. (Kansas Agricultural Experiment Station, 2011)
Seventy head of fed Hereford steers, sired by four different bulls, were slaughtered in Kansas City, and the rib cut from 40 (10 for each sire) returned to Manhattan for detailed analysis. Cooking data are now available on the ribs and are being prepared for the Statistical Laboratory, along with other data. All steers graded Choice on foot, but only three graded Choice in the carcass due to lack of marbling. The following table gives gross measure of the observations.
Keywords: Beef; Sire; Quality; Carcass characterisitcs